Airport grating as a fast and effective method of improving the load-bearing capacity of natural airport pavements - Agata Kowalewska; Pawel Pietruszewski; Krzysztof Blacha (Przegląd Komunikacyjny)
Abstract: Natural airport surfaces, which are functional elements of airports, such as: runway shoulders, frontal lanes, emergency runway, or working runway, play an important role in the safety of air operations. Both the International Civil Aviation Organization (ICAO) and the European Union Aviation Safety Agency (EASA) define the load-bearing capacity requirements that natural airport pavements should meet. These documents specify the required California Bearing Ratio (CBR) of 15-20% at a depth of 15 cm below ground level. The previous field tests in civil and military airports have shown that the load-bearing capacity of natural airport pavements sometimes does not meet certain requirements. Due to the fact that airports cannot afford to shut down the airport for a long time, it is reasonable to search for innovative methods of improving the load-bearing capacity of natural airport pavements, which will be effective and quick to implement. Such a method may be the use of an airport grating pressed directly into the natural airport pavement. Keywords: Load capacity; CBR; Natural airport pavement; Safety of air operations